2011
DOI: 10.1002/ijc.25767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interferon treatment on development and progression of hepatocellular carcinoma in patients with chronic virus infection: A meta‐analysis of randomized controlled trials

Abstract: Available literature on the effects of interferon (IFN) treatment on development and progression of hepatocellular carcinoma (HCC) in patients with chronic virus infection reports controversial results. The primary objective of this meta-analysis was to evaluate the effect of IFN on HCC risk in patients with chronic hepatitis C virus (HCV) or hepatitis B virus (HBV) infection; IFN's efficacy on local tumor progression and survival of advanced HCC patients was also assessed. All randomized controlled trials (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Several meta-analyses have examined the relationship between achievement of SVR and subsequent development of HCC (18,(22)(23)(24)(25)(26). Although these studies universally agree that SVR is strongly associated with a reduction in HCC, especially among persons who have progressed to advanced liver disease, the degree to which this association is true remains uncertain.…”
mentioning
confidence: 99%
“…Several meta-analyses have examined the relationship between achievement of SVR and subsequent development of HCC (18,(22)(23)(24)(25)(26). Although these studies universally agree that SVR is strongly associated with a reduction in HCC, especially among persons who have progressed to advanced liver disease, the degree to which this association is true remains uncertain.…”
mentioning
confidence: 99%
“…Finally, since there is definitely no agreement on the efficacy and cost/effectiveness of antiviral treatment, whether IFN or NA, in HCC prevention (Asia-Pacific Working Party, 2010;Colombo, 2010;Liaw, 2010;Zhang et al, 2011), there is a need of well-constructed, large size, randomized prospective trials to confirm what is still based more on experts' opinions than on a sound scientific evidence, despite the number of studies published on the topic.…”
Section: Resultsmentioning
confidence: 97%
“…8 Another report showed that the relative risk reduction of overall HCC incidence associated with interferon therapy was 77% in HBV-infected patients and 61% in HCV-infected patients. 16 From Taiwan Cancer Registry, 15 we know that there were about 300 incident HCC cases among men aged 30-39 in 2003. If the trend remained unchanged, there should have been 1500 new HCC cases from 2003 to 2007.…”
Section: Discussionmentioning
confidence: 98%